A educação ambiental nas escolas municipais de educação infantil de São Carlos-SP - Fagionato-Ruffino, Sandra (Universidade Federal de São Carlos, 2003)
We now live immersed in an environmental crisis that resulted from the development model that was adopted — Environmental Education is an important process to help revert such a crisis and re-establish a sustainable ecosystem. Brazilian public policies since 1981 guarantee every citizen the right to Environmental Education, and emphasize the responsibility of schools in the process, on ali leveis from pre-schooi to graduate schools. Among ali different education leveis, pre-school and kindergarten present the biggest shortage in materiais, courses and published work in the area. In that context, this research work's objective is to know the reality in the Municipal Pre-schools and Kindergarten schools in São Carlos when it comes to Environmental Education (EE), and to identify who the teachers are, what they think about, and what they do about EE, what resources and themes are most often adopted, as well as what are the difficulties and elements that facilitate the incorporation of EE in the school day to day. A questionnaire was the main instrument in collecting data, due to the possibility of reaching a large number of teachers. Observations of the day to day in schools and teachers' planning sessions were also used. From the analysis of the data the conclusion can be reached that the majority of the teachers we studied have a very traditional conception ofEnvironmental Education, associated to the teaching of Sciences, with an emphasis in the detection and, sometimes, resolution of the environmental problems. The themes and experiments most often chosen have to do with solid waste and flora. The majority of the teachers work the subject from the projects, but also use day to day situations. Holidays are also used by the teachers to work the subjects, sometimes on the day, sometimes inserted in a monthly or bi-monthly plan that celebrates the occasion. Teachers most often point to the lack of infrastructure and knowledge as stumbling blocks to the incorporation ofEE in school.
Environmental education in the municipal schools of early childhood education of São Carlos-SP
Keywords: Educação ambiental; Educação infantil; Práticas pedagógicas; Environmental Education; Pre-School and Kindergarten; Pedagogy; CIENCIAS HUMANAS::EDUCACAO